Parallel Linear Hashtable Motion Estimation Algorithm - Yunsong Wu; Megson, G. (2006 16th IEEE Signal Processing Society Workshop on Machine Learning for Signal Processing, 2006)
This paper presents a parallel linear hashtable motion estimation algorithm (LHMEA). Most parallel video compression algorithms focus on group of picture (GOP). Based on LHMEA we proposed earl[1][2], we developed a parallel motion estimation algorithm focus inside of frame. We divide each reference frames into equally sized regions. These regions are going to be processed in parallel to increase the encoding speed significantly. The theory and practice speed up of parallel LHMEA according to the number of PCs in the cluster are compared and discussed. Motion vectors (MV) are generated from the first-pass LHMEA and used as predictors for second-pass hexagonal search (HEXBS) motion estimation, which only searches a small number of Macroblocks (MBs). We evaluated distributed parallel implementation of LHMEA of TPA for real time video compression.